2009
DOI: 10.1007/s00125-009-1437-1
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycaemia and cognitive impairment in older patients with diabetes: the Fremantle Diabetes Study

Abstract: Aims/hypothesis The aim was to investigate the relationship between severe hypoglycaemia and cognitive impairment in older patients with diabetes. Methods A sample of 302 diabetic patients aged ≥70 years was assessed for dementia or cognitive impairment without dementia in 2001-2002 and a subsample of non-demented patients (n=205) was followed to assess cognitive decline. A history of severe hypoglycaemia was determined from self-reports, physician assessments and records of health service use for hypoglycaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
118
1
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(143 citation statements)
references
References 31 publications
(51 reference statements)
12
118
1
10
Order By: Relevance
“…1,25 As mentioned, older persons with dementia are less able to effectively manage complex treatment regimens because of behavioral impairments, and, thus, recognize the symptoms of hypoglycemia and respond appropriately, increasing the risk for severe hypoglycemia. 2,5,17,25 Indeed, our findings confirmed that severe hypoglycemia was more prevalent among patients with dementia compared with patients without dementia. There is evidence that neuronal damage resulting from hypoglycemia is more vulnerable in those with diabetes, perhaps due to altered glucose metabolism.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…1,25 As mentioned, older persons with dementia are less able to effectively manage complex treatment regimens because of behavioral impairments, and, thus, recognize the symptoms of hypoglycemia and respond appropriately, increasing the risk for severe hypoglycemia. 2,5,17,25 Indeed, our findings confirmed that severe hypoglycemia was more prevalent among patients with dementia compared with patients without dementia. There is evidence that neuronal damage resulting from hypoglycemia is more vulnerable in those with diabetes, perhaps due to altered glucose metabolism.…”
Section: Discussionsupporting
confidence: 82%
“…2,3 However, this study did not test for different risks according to specific types of insulin or oral antidiabetic agents, probably because of the small study size (n ¼ 28). 2,3 Older nursing home patients represent a specific population of very frail individuals who need assistance in performing daily activities. Nursing home patients are closely monitored, and medically verified severe hypoglycemia is a validated finding compared with self-reported measures often used in community-dwelling population studies.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[13][14][15] Patients with dysphasia may find it difficult to explain hypoglycaemic episodes even if they recognise it in the first place. Regular monitoring of the meter and discussions with carers should help highlight these episodes.…”
Section: Effect Of Dementia On Diabetes Managementmentioning
confidence: 99%